A regime shift from erosion to carbon accumulation in a temperate northern peatland. (14th August 2020) - Milner, Alice M.; Baird, Andy J.; Green, Sophie M.; Swindles, Graeme T.; Young, Dylan M.; Sanderson, Nicole K.; Timmins, Madeleine S. I.; Gałka, Mariusz
Abstract: Peatlands are globally important ecosystems but many are degraded and some are eroding. However, some degraded peatlands are undergoing apparently spontaneous recovery, with switches from erosion to renewed carbon accumulation—a type of ecological regime shift. We used a palaeoecological approach to investigate and help understand such a switch in a blanket peatland in North Wales, UK. Our data show: (a) a rapid accumulation of new peat after the switch from the eroding state, with between 5.2 and 10.6 kg/m 2 carbon accumulating since the beginning of the recovery which occurred between the late 1800s and early to mid‐1900s CE, with an average carbon accumulation rate in the new peat between 46 and 121 g C m −2  year −1 ; (b) three main successional pathways in peat‐forming vegetation and (c) hydrological changes with an increase to moderately high water‐tables after the switch that promoted new carbon accumulation as well as protecting vulnerable old carbon. External factors, including changes in climate and industrial activity, can only partially explain our results. Following previous studies, we suggest that internal ecosystem processes offer a substantial part of the explanation and interpret the switch to renewed carbon accumulation as a bifurcation‐type tipping point involving changes in the physical form of the eroded landscape. Synthesis . Our long‐term ecological data reveal a switch from a degraded peatland with active erosion and loss of carbon to a revegetated, wetter peatland accumulating carbon. The switch can be interpreted as a bifurcation tipping point. We suggest that external factors such as climate and pollution levels are important for setting suitable boundary conditions for peatland recovery, but internal mechanisms can explain the change in peatland state. Our study is the first of its kind to apply tipping point theory to the internal mechanisms linked to peat erosion and recovery and may help improve understanding of the trajectories of other peatlands in a changing climate. Abstract : Long‐term ecological data reveal a switch from a degraded peatland with active erosion and carbon loss to a revegetated peatland accumulating carbon. The switch can be interpreted as a bifurcation tipping point. We suggest that external factors such as climate and pollution levels are important for setting suitable boundary conditions for peatland recovery, but internal mechanisms can explain the change in peatland state.